FAILURE OF GEOTHERMAL EXPLORATION IN BATURADEN IN A GREEN CRIMINOLOGY PERSPECTIVE - Arif Awaludin (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Geothermal is one of the renewable energy sources that will contribute to the energy mix in Indonesia. Geothermal exploration is mostly carried out in forest areas in Indonesia. Many problems arise. The failure of geothermal exploration in Baturaden since 2017 has left two unproductive wells. Land clearing, logging and contamination of ground water are part of the destruction caused. A Green Criminology approach is needed to uncover various potential crimes that arise and their prevention. Qualitative analysis is used to help reveal in detail the potential crimes that occurred. A comprehensive policy is needed to tackle environmental crimes in connection with geothermal exploration in Indonesia. The issuance of Law on Environmental Protection and Management Number 32 of 2009, Law Number 21 of 2014 concerning Geothermal and Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction needs to be harmonized so that environmental law enforcement policies become more effective and efficient.